The Energy Union and European Union energy security - Zajączkowska, Magdalena (Ekonomia i Prawo. Economics and Law, 2018)
Motivation: The idea of EU Energy Union was presented in 2014 as a response to the deepening energy crisis with the main gas supply partner, Russia. In 2015 and in 2017 European Commission presented the state of the Energy Union, which shows progress made since the Energy Union Framework Strategy was adopted. It was planned that in 2016 Energy Union would be fully implemented. The Energy Union is based on the three objectives of EU climate and energy policy: security of supply, sustainability and competitiveness. To reach these objectives the Energy Union focuses on five mutually supportive dimensions: 1) energy security, solidarity and trust; 2) a fully integrated European energy market; 3) energy efficiency contributing to moderation of demand; 4) decarbonising the economy and 5) research, innovation and competitiveness. Aim: The objective of this article is to analyse the current state of the implementation of the first objective of the Energy Union: energy security, solidarity and trust in the context of the energy strategies of selected EU countries. Results: None from the Member States was against the Energy Union project, but each of them understands this term differently. Full implementation of the concept is in contradiction with the energy policies of some Member States, mainly the big players. There are no concrete solutions to the implementation of instruments to enhance energy security.